1994
DOI: 10.1007/bf00006902
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and process in the biogeography of subterranean amphipods

Abstract: The comparative data from studies of two 'superfamily' groups with large numbers of subterranean taxa, the exclusively freshwater Crangonyctoidea and the predominately marine Hadzioidea, support the hypothesis that distributional patterns and evolutionary processes of stygobiont amphipods are closely linked and that the former can be a useful indicator of the latter. Three major biogeographic patterns are indicated by the distribution of subterranean species in these groups, each apparently reflecting a partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 18 publications
2
49
0
1
Order By: Relevance
“…Ainsi, en Amérique de nombreuses études ont été entreprises, notamment par Bousfield (1958), Maguire (1964), Holsinger (1972Holsinger ( , 1986Holsinger ( , 1994Holsinger ( , 2000, Culver (1982), Koenemann & Holsinger (2001), et en Afrique subsaharienne par Magniez (1979) et récem-ment par Zébazé-Togouet et al (2009).…”
Section: Introductionunclassified
“…Ainsi, en Amérique de nombreuses études ont été entreprises, notamment par Bousfield (1958), Maguire (1964), Holsinger (1972Holsinger ( , 1986Holsinger ( , 1994Holsinger ( , 2000, Culver (1982), Koenemann & Holsinger (2001), et en Afrique subsaharienne par Magniez (1979) et récem-ment par Zébazé-Togouet et al (2009).…”
Section: Introductionunclassified
“…Areas presently land that were ever covered by the DOI: 10.18195/issn.0313-122x.64.2001.063-083 sea, even as far back as the Mesozoic, often contain communities of obligate subterranean aquatic species of formerly marine lineages 'stranded' inland by marine recession (Stock, 1980;Boutin and Coineau, 1990;Notenboom, 1991;Holsinger, 1994), particularly in karst areas. This is especially nota~le in regions that have undergone substanhal orogenesis (Messouli et al, 1991;Boutin, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…When comparing this amphipod diversity across geographical regions, the Caribbean has a larger diversity than the Patagonian Shelf (98 species) and the Tropical West Atlantic (107 species taxa, whose present distribution and biogeographic pattern reflect their origin. In the case of marine and brackish species, it has been suggested that they may have derived from epigean marine or brackish water ancestors as they adapted to fluctuating sea levels, and even some freshwater species may have derived from marine and brackish species that were caught inland during regression of seawater (Holsinger, 1994;Biernbaum, 1996), in both cases leading to speciation by isolation.…”
Section: Discussionmentioning
confidence: 99%